Effect of Surgical Repair Of Buried Penis On Erectile Function Among Children - Mohamad, Abdelhalem Shawkat; Sabra, Tarek Abdelazeem; Abdelhakeem, Omar Nagy; Fathy, Khalaf Yassen; Nagaty, Mohamed Ahmed Mohamed; Moustafa, Alaa Ahmed Elsayed (Journal of Neonatal Surgery, 2025)
Background: Buried penis in children is a congenital anomaly characterized by a normal sized penis which is retracted within pre pubic tissue. several scholars have researched surgical treatment of buried penis in children. The aim of this study to compare between surgical repair of buried panis by degloving only and degloving without fixation as regards erectile function. Patient and methods: Clinical data of 10 patients with buried penis who were treated using the degloving only technique were retrospectively collected, analyzed and compared, with Clinical data of 10 patients with buried penis who were treated using degloving with fixation technique in pediatric surgery unit at Minia during the period from 2020 to 2022. Results: No significant difference between surgical groups regards early and post-operative follow-up data. There was significant improvement of apparent penile length in both surgical groups before and after surgery. Erectile function was positive in both surgical groups. Regarding parent satisfaction it was higher in the degloving with fixation group than degloving only. Conclusion: Early recognition of buried penis is certainly the key to prompt treatment, as is the local and regional awareness of reconstructive service provision the postoperative length and function of the penis of patients with buried penis are significantly improved compared with those before the operation.